Cardiac surgeryLong-term results after concomitant cardiac surgery and pulmonary resection - Kogan, Alexander; Rocah, Merav; Preisman, Sergey; Lavee, Jacob; Simansky, David; Nun, Alon Ben; Raanani, Ehud; Sternik, Leonid (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Concomitant lesions of the heart and lung are uncommon, but when present they pose a challenge for cardiac and thoracic surgeons. Patients with lung cancer and heart disease are at a high risk for postoperative death or severe cardiovascular complications. Aim of the study: To report our results of concomitant cardiac surgery and lung resection. Material and methods: From 1994 to 2012, 18 patients with cardiac disorders and lung cancer or another lung disease were operated on. Twelve patients underwent coronary artery bypass grafting, 3 patients underwent aortic valve replacement and 3 patients underwent another cardiac surgery procedure. The pulmonary resections consisted of pneumonectomy in 1 patient, lobectomy in 6 patients and wedge excision in 10 patients. Follow-up was obtained for all 18 patients (mean follow-up 70.6 months; range 224 to 0.7 months). Results: The pathologic examination confirmed lung malignancy in 12 patients. Five patients were operated on due to a non-oncologic pathology and 1 patient underwent lung volume resection. Overall late survival was 88% and 67% at 1 and 5 years, respectively. Conclusions: Lung resection carried out concomitantly with cardiac surgery is safe and effective. A combined procedure avoids the need for a second major thoracic procedure and may improve clinical outcome.